Coupled Invariant Point Theorems in Bicomplex Parametric Partial Metric Space Amongst Dominate Function - Namdev, Rakhi; Tiwari, Rashmi; Singh, Umashankar; Bhardwaj, Ramakant (Communications in Mathematics and Applications, 2024)
In this paper, bicomplex parametric partial metric space is discussed. The new contractive condition is discussed for coupled invariant point concerning self-mapping on the said spaces with particular conditions. We support our tracking down through models. Our outcomes sum up the common coupled invariant point in bicomplex valued parametric metric spaces by Saluja (Coupled fixed point results based on control function in complex partial metric spaces, Functional Analysis, Approximation and Computation 15(2) (2023), 1 – 15). Established results generalize previously known results for specified conditions.
Keywords: Bicomplex Parametric Partial Metric Space (BCPPMS); Dominate function; Coupled invariant point; Generalized contraction conditions